2021
DOI: 10.4049/jimmunol.2000624
|View full text |Cite
|
Sign up to set email alerts
|

NFAT5 Amplifies Antipathogen Responses by Enhancing Chromatin Accessibility, H3K27 Demethylation, and Transcription Factor Recruitment

Abstract: The ability of innate immune cells to respond to pathogen-associated molecular patterns across a wide range of intensities is fundamental to limit the spreading of infections. Studies on transcription responses to pathogen-activated TLRs have often used relatively high TLR ligand concentrations, and less is known about their regulation under mild stimulatory conditions. We had shown that the transcription factor NFAT5 facilitates expression of antipathogen genes under TLR stimulation conditions corresponding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Mechanically, as a transcription factor, p65 could bind to two binding sites (-591 ~ -582 nt and -299 ~ -290 nt) of IRF-8 gene promotor and increase IRF-8 gene transcription. Here, it is worthy to mention that, since reportedly p65 triggers the transcription of some pro-inflammatory genes such as IL-6, TNF-α and CXCL5 56 , 57 , and serval p65-binding sites are predicted in CCL3 gene promotor, we speculate that p65 could activate CCL3 gene in rat GMCs directly. Thus, we did further experiments, and found that p65 knockdown in the GMCs did not reduce CCL3 gene transcription induced by IRF-8 overexpression, suggesting that p65 does not directly trigger CCL3 gene transcription in the GMCs.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Mechanically, as a transcription factor, p65 could bind to two binding sites (-591 ~ -582 nt and -299 ~ -290 nt) of IRF-8 gene promotor and increase IRF-8 gene transcription. Here, it is worthy to mention that, since reportedly p65 triggers the transcription of some pro-inflammatory genes such as IL-6, TNF-α and CXCL5 56 , 57 , and serval p65-binding sites are predicted in CCL3 gene promotor, we speculate that p65 could activate CCL3 gene in rat GMCs directly. Thus, we did further experiments, and found that p65 knockdown in the GMCs did not reduce CCL3 gene transcription induced by IRF-8 overexpression, suggesting that p65 does not directly trigger CCL3 gene transcription in the GMCs.…”
Section: Discussionmentioning
confidence: 73%
“…It has been documented that the cells stimulated with external stimulants can rapidly turn on some signal transduction pathways and up-regulate some transcription factors , leading to corresponding target gene expression 56 , 57 . Subsequently, in order to find the upstream regulatory molecules of IRF-8-mediated CCL3/4 production in Thy-1N, we examined the phosphorylation (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The cell culture model mimicked the in vivo findings as exposure to hypoxia amplified Pdgfb expression and the release of PDGFB in Nfat5 -/- versus Nfat5 fl/fl MLEC (Figure 4A-C). Although stimulation of gene expression upon knockout of a transcription factor seems counterintuitive, NFAT5 has been reported to alter transcriptional activity by modulating DNA methylation and chromatin accessibility 25 as well as by inhibiting recruitment of transcription factors to enhancer regions of gene promoters 26 . As our results did not substantiate an impact of NFAT5-mediated DNA methylation (Supplement 21) or chromatin accessibility (Supplement 22) on Pdgfb expression under the tested experimental conditions, we investigated whether binding of HIF1α - a transcription factor that is crucial for hypoxia-induced Pdgfb expression in MLEC (Supplement 23) 6 - to the Pdgfb promoter is altered in the presence or absence of NFAT5.…”
Section: Resultsmentioning
confidence: 99%
“…qPCR was performed to determine the enrichment of protein-bound DNA. Detailed primer and antibody information can be found in Tables S1 and S2 [45][46][47].…”
Section: Chip-qpcrmentioning
confidence: 99%